Pemaknaan Kata ‘Babi’ dalam Pendidikan Masyarakat Kontemporer (Studi Semiotika Novel Jakarta Sebelum Pagi) - Meychel Salsabyla; Putri Retnosari (Universitas Negeri Yogyakarta, 2026)
This study aims to discover the essence of the meaning of the word Babi, which represents a symbol of human attitudes in the world and is represented in the novel Jakarta Sebelum Pagi by Ziggy Zezsyazeoviennazabrizkie. The analysis is conducted through a study of Roland Barthes' semiotic theory which includes denotation, connotation, and myth. In addition, this research is motivated by the various meanings formed from the use of the word Babi in the novel, as well as the social myths that emerge behind the word Babi. The method used is descriptive qualitative with reading, note-taking, data reduction, and theory triangulation techniques. The results of the study show that the word Babi does not only function as a curse or animal name, but forms a social classification system consisting of nine categories, namely yan pi, babi bakar, babi steril, babi kacung, babi rakyat, babi aristocrat, babi Animal Farm, babi jahanam, and babirusa. Each category represents a certain social position in urban life in Jakarta. At the myth level, the sign system shows how social inequality is considered something normal in everyday life. This research also found that the meaning of the word Babi is constructed through cross-media references, ranging from Japanese manga to George Orwell's novel Animal Farm..